The effects of appearance and intellectual disability identification on perceptions of and affective and behavioral intentions toward individuals with intellectual disabilities - McManus, Jessica Lynn (Kansas State University, 2010)
Research has shown that attributions and behavioral reactions toward individuals may be based on their appearance; our studies examined how appearance-based assessments for individuals with intellectual disabilities (IDs) determined how others think and react toward a target individual. Two studies examined the effects of appearance and identification on perceptions (i.e., agentic and communal traits) and behavioral reactions (i.e, self-efficacy expectations, anxiety, willingness to interact) toward targets. Studies 1 and 2 demonstrated that individuals with atypical appearances were rated higher on communal than agentic traits. Study 2 revealed that greater self-efficacy expectations and lower anxiety were associated with individuals with atypical appearances and individuals identified as having an ID. These studies increase understanding of perceiver-focused and target-focused factors related to bias toward individuals with IDs.
Keywords: Intellectual disabilities; Perceptions; Education, Special (0529); Psychology, General (0621); Psychology, Social (0451)